Black phosphorene: A versatile allotrope revolutionizing environmental, energy, and biomedical applications - Mishra S.R.; Gadore V.; Chavda V.; Panda S.; Roy S.; Sahoo P.; Pradhan L.; Rai H.; Pandey S.S.; Ahmaruzzaman M. (My University, 2025)
Black phosphorene (BP), an exciting allotrope of phosphorus, has sparked widespread attention owing to its unique physicochemical characteristics and numerous potentials in the environmental, energy, and biological sectors. The current review delves further into BP, concentrating on its layered structure, unusual features, and broad applications. Methods of synthesis of BP, such as liquid exfoliation, chemical vapor deposition, and mechanical exfoliation, are reviewed, and characterization procedures critical to ensuring the quality of BP are described. Its anisotropic mechanical, electrical, and optical properties are investigated using insights gained from its hexagonal lattice atomic structure and puckered layers. In environmental contexts, BP shows potential for water purification due to its strong adsorption and degradation capabilities against various contaminants, including dyes, medicines, pesticides, heavy metals, and organic compounds. Its potential in environmental sensing is also emphasized, notably for detecting gasses, heavy metals, and pollutants. Moving on to energy applications, BP is used in batteries, supercapacitors, and hydrogen generation, where its unique electrical and structural properties improve energy storage and conversion efficiency. BP improves medication delivery systems in biomedical applications by providing biocompatibility and customizable delivery capabilities. Furthermore, its biological imaging and diagnostics applications are reviewed, focusing on optical properties and contrast enhancement capabilities. Nonetheless, despite BP's significant potential, serious hurdles persist. Issues including stability under ambient settings, large-scale synthesis limits, and biocompatibility difficulties require resolution for more considerable practical use. The paper concludes by exploring future challenges and solutions to motivate readers. In summary, BP stands as a flexible material prepared to drive innovation in environmental, energy, and biological applications, although attaining its revolutionary influence will depend on overcoming present technological, scientific, and scaling limitations. © 2024 Elsevier B.V.